An evaluation study on ASP textbook 'Advanced Media Arabic' - Chik, Abdul Rahman; Tg Abdul Rahman, Tg Ainul Farha (2012)
The objectives of this paper are two folds: firstly, to highlight the systematic approach adopted in evaluating an ASP textbook and secondly, to report the status of an ASP textbook "Advanced Media Arabic". for this purpose the paper adopts analytical method, with analyzing Arabic experts' comments and suggestions towards the proposed criteria of the evaluation tool. The tool was initially developed by Rushdi To'eima in evaluating Arabic textbooks and then extensively developed by a group of researchers and IIUM post graduate students. The paper also adopts evaluation method in assessing the "Advanced Media Arabic". The discussion in this paper will have three main parts; the first is with its focus on development of evaluation tool, the second is on the methodology and the procedure of evaluation study, while the last will present the findings of this study. The paper will highlight the strengths and weaknesses of the book as well as putting some technical advice and suggestions to improve the book's quality.